Relationship Between Vein Graft Failure and Subsequent Clinical Outcomes After Coronary Artery Bypass Surgery - Lopes, Renato D. (2012)
BACKGROUND: Vein graft failure (VGF) is common after coronary artery bypass graft surgery, but its relationship with long-term clinical outcomes is unknown. In this retrospective analysis, we examined the relationship between VGF, assessed by coronary angiography 12 to 18 months after coronary artery bypass graft surgery, and subsequent clinical outcomes. METHODS AND RESULTS: Using the Project of Ex Vivo Vein Graft Engineering via Transfection IV (PREVENT IV) trial database, we studied data from 1829 patients who underwent coronary artery bypass graft surgery and had an angiogram performed up to 18 months after surgery. The main outcome measure was death, myocardial infarction, and repeat revascularization through 4 years after angiography. VGF occurred in 787 of 1829 patients (43%). Clinical follow-up was completed in 97% of patients with angiographic follow-up. The composite of death, myocardial infarction, or revascularization occurred more frequently among patients who had any VGF compared with those who had none (adjusted hazard ratio, 1.58; 95% confidence interval, 1.21–2.06; P=0.008). This was due mainly to more frequent revascularization with no differences in death (adjusted hazard ratio, 1.04; 95% confidence interval, 0.71–1.52; P=0.85) or death or myocardial infarction (adjusted hazard ratio, 1.08; 95% confidence interval, 0.77–1.53; P=0.65). CONCLUSIONS: VGF is common after coronary artery bypass graft surgery and is associated with repeat revascularization but not with death and/or myocardial infarction. Further investigations are needed to evaluate therapies and strategies for decreasing VGF to improve outcomes in patients undergoing coronary artery bypass graft surgery.